Bank Wakaf Mikro: The operations and its role towards Islamic Good Governance in Pandemic Era - Rofiqoh, Siti Nur Indah; Sukmana, Raditya; Ratnasari, Ririn Tri; Nafik HR, Muhammad; Rufaidah, Anik; Ala’uddin, Muhammad (International Conference on Sustainable Health Promotion, 2021)
There are many cash waqf institutions in East Java such as Islamic boarding school micro waqf banks with an entrepreneurial basis, but they have many problems, including transparency, accountability, Nazhir's professionalism, marketing, accessibility, asset misuse, responsibility, risk analysis skills, underwriting supervision and lack of support and participation. government. The purpose of this study is to holistically analyze the effective Islamic Good Governance (IGG) in Islamic boarding school waqf banks. The research was conducted qualitatively with a multiple case studies approach in six cash waqf institutions in East Java. It was concluded that the ICG in the six institutions had similarities in the management of funds using qardh which were distributed to the productive poor around the Islamic boarding school by mobilizing the entire team in the institution. No one collects waqf funds directly because only LAZNAS BSM Umat has the authority